2019
DOI: 10.3390/ijerph16152671
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Nutritional Quality and Cognitive Interference in University Students from Mexico City

Abstract: Skipping breakfast might have an impact on cognitive functions, such as interference, which is a basic capacity of executive functions that denotes the possibility of controlling an automated response. This study aimed to analyze the association between nutritional quality of breakfast and cognitive interference in a sample of university students. A cross-sectional study was conducted, a total of 422 students between 18 and 25 years participated. Cognitive interference was assessed with the Stroop Test. Breakf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…It is well known that a high-quality breakfast is a great source of amino acids, vitamins, minerals, antioxidants, and fiber, which positively impacts children’s global health and cognition [ 5 , 6 , 7 ]. In this way, evidence indicates that breakfast composition may affect behavior, cognition, and learning in children and adolescents [ 47 , 48 , 49 , 50 ]. In our study, both cereals and fruits (and fruit juices without added sugar) were not associated with significant cognitive performance differences.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a high-quality breakfast is a great source of amino acids, vitamins, minerals, antioxidants, and fiber, which positively impacts children’s global health and cognition [ 5 , 6 , 7 ]. In this way, evidence indicates that breakfast composition may affect behavior, cognition, and learning in children and adolescents [ 47 , 48 , 49 , 50 ]. In our study, both cereals and fruits (and fruit juices without added sugar) were not associated with significant cognitive performance differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that regular breakfast consumption is associated with increased intelligence quotient (IQ) in kindergarten children [ 3 ]. Since our report, several studies examining the relationship between breakfast and cognition have published mixed findings [ 6 , 7 , 8 ], demonstrating a need for improved methodology and further evaluation of breakfast composition to evaluate potential nutritional corollaries to observed outcomes. First, studies on breakfast consumption and cognitive function have largely been cross-sectional, which by nature, eliminates the author’s ability to determine the directionality of the relationship.…”
Section: Introductionmentioning
confidence: 95%
“…Penelitian yang dilakukan oleh Sünram-Lea (2019) mengenai dampak respon glikemik berbasis sarapan pada kognisi menunjukkan bahwa profil glukosa darah yang lebih stabil bersirkulasi dikaitkan dengan fungsi kognitif yang lebih baik di pagi hari. Melewatkan sarapan mungkin berdampak pada fungsi kognitif, seperti gangguan kapasitas dasar fungsi eksekutif dalam mengendalikan respons otomatis (Sámano et al 2019).…”
Section: Pendahuluanunclassified